2019
DOI: 10.1182/bloodadvances.2018020602
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and tumor-associated macrophages in de novo DLBCL

Abstract: Programmed death-ligand 1 (PD-L1) and its receptor, programmed cell death-1 (PD-1), are important negative regulators of immune cell activation. Therapeutically targeting PD-1/PD-L1 in diffuse large B-cell lymphoma (DLBCL) patients with a single agent has limited activity, meriting a deeper understanding of this complex biology and of available PD-L1 clinical assays. In this study, we leveraged 2 large de novo DLBCL phase 3 trials (GOYA and MAIN) to better understand the biologic and clinical relevance of PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 48 publications
11
76
1
Order By: Relevance
“…12 In contrast, others found that PD-L1 was expressed in some DLBCL tumour cells. [8][9][10][11] Our results support the latter findings.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…12 In contrast, others found that PD-L1 was expressed in some DLBCL tumour cells. [8][9][10][11] Our results support the latter findings.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this, overexpression of PD‐L1 in tumour cells has been identified as an independent adverse prognostic marker associated with inferior outcome in several studies including studies of DLBCL . However, one study suggests an association of PD‐L1 and better prognosis in some de novo DLBCL patients …”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations